(untitled) (Fiep Bulletin - online, 2011)
Introduction: The shoulder is the harmonious combination of five joints (glenohumeral, acromioclavicular and sternoclavicular joint, subacromial joint, scapulothoracic articulation) that characterize the shoulder girdle. The movement of these joints in sync requires a joint painless and without injury. The top of the humeral head is covered with a hood tendon resulting from the termination of the tendons of the subscapularis, the front, above the supraspinatus, infra-spinal and teres minor behind. This hood tendon adheres closely to the joint capsule, forming a cover over the humeral head, hence the name "rotator cuff". One of the main functions of the rotator cuff is to enable the rotation of the shoulder. Another function of the rotator cuff to stabilize the top of the shoulder joint.The objective of this research was to: identify the índex lesion of the rotador cuff in practice gymnastics Academy Equilibrium neighborhood Ponta Verde, Maceió-AL. Methodology: This study considered the Norms for Research Using Human Subjects, Resolution 196/96 of the National Health Council of 10/10/1996 (BRAZIL, 1996). After being submitted to the ethics committee of the Faculty of Alagoas was approved under the Protocol 016/09. Analysis and discussion of results after sixteen weeks (16) weeks of intervention and administering the scale UCLA last (University of California at Los Angeles Shoulder Rating Scale) was found that the two hundred sixty-one students (261) enrolled, eighty-four (84) are male one hundred and seventy-seven are female (177). Aged between 18 and 45 years of age.It was found that the eighty-four (84) men, two (02) had pain in the knee joint and shoulder, one (01) had pain in the trapezius and one (01) had pain in the shoulder and lumbar spine. Conclusion: It can be concluded that after practice gymnastics academy Equilibrium be submitted to the study, there was no damage to the rotator cuff, it is suggested that further research be carried out in other gyms of Miami, which includes the female audience.